Deciphering the role of functional synergy in a catalytic molecular assembler: a proof of concept for boosted catalysis via retrosynthetic linker scissoring. (30th January 2023) - Goswami, Ranadip; Karmakar, Arun; Rajput, Sonal; Singh, Manpreet; Kundu, Subrata; Neogi, Subhadip
Abstract : Retrosynthetic scissoring of functional backbone in an ultra-robust MOF leads devising unique catassembler as a blueprint of molecular machine for advanced electrochemical OER and hydrogen-bond-donating catalysis. Abstract : Artificial catalytic machinery enables improvising purpose-driven pore functionality engineering in metal–organic frameworks (MOFs) in pursuit of renewable energy sources and biomimetic hydrogen-bond-donating (HBD) organo-catalysis. Though challenging, systematic functional-tagging via bottom-up Lego® chemistry in such materials is highly sought and obligates a coherent design principle of self-assembly to resolve these alarming issues. We demonstrate a unique linker scissoring strategy to develop an ultra-robust MOF with redox-active Co(ii ) nodes from electroactive and H-bond operative struts, which exemplifies the unprecedented alliance of bimodal sustainable catalysis via tandem functionality installation over a single, multifaceted platform. The framework displays highly efficient and durable oxygen evolution reactions (OERs) in alkaline media with notable electrocatalytic parameters that rank among the best-known MOFs and even outperforms some benchmark catalysts. This microporous vessel further delineates the rarest –NH2 -hook-mediated recyclable Friedel–Crafts alkylation of indole and β-nitrostyrene via mild-condition HBD reactions and exhibits molecular-dimension-mediated size selectivity. The synergistic involvement of facile charge transfer in electrochemically dynamic linkers and favourable two-point H-bonding in pendent ligands underpins individual catalytic efficiency as elaborated via analyte-induced concomitant fluorescence modification and variable control experiments. Significantly, the key roles of task-specific sites in both OERs and HBD catalysis are validated from juxtaposing the performance of three isostructural Co(ii ) MOFs via the cooperative functional assembly of retrosynthetically fragmented MOFs. This novel strategy of sequential trimming of the functional backbone comprehensively demonstrates the superiority of the present system and leads to devising a unique catassembler as a blueprint of futuristic molecular machines for improved catalytic direction.